2018
DOI: 10.1097/md.0000000000013789
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific and gender-dependent impact of primary headache disorders on dementia risk

Abstract: Dementia is a global burden of public health. Headache disorders are the third most common cause of disability worldwide and common problems in the elderly population. Few studies focused on the relationship between primary headache disorders (PHDs) and cognitive status, and the results remain controversial. The aim of this countrywide, population-based, retrospective study was to investigate potential association between PHDs and dementia risk.We enrolled 1346 cases with PHDs to match the 5384 individuals by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Additional evidence supports an association of dementia with headaches overall (including migraines) and nonmigrainous headaches . However, the association between migraines and dementia was significant only among women in models stratified by gender: this same gender effect was observed for all headaches and nonmigrainous headaches . The present study reflected this strong association of migraines with dementia in women; it was unable to assess potential gender differences because no male participants had dementia as well as a history of migraines.…”
Section: Discussionmentioning
confidence: 39%
See 4 more Smart Citations
“…Additional evidence supports an association of dementia with headaches overall (including migraines) and nonmigrainous headaches . However, the association between migraines and dementia was significant only among women in models stratified by gender: this same gender effect was observed for all headaches and nonmigrainous headaches . The present study reflected this strong association of migraines with dementia in women; it was unable to assess potential gender differences because no male participants had dementia as well as a history of migraines.…”
Section: Discussionmentioning
confidence: 39%
“…The significant increased risk of dementia with migraines noted in this study is consistent with those of other cohort studies 9,11,13 and in contrast with other individual studies 12 and a meta-analysis of cohort studies 7 that found no association. Additional evidence supports an association of dementia with headaches overall (including 12,13 However, the association between migraines and dementia was significant only among women in models stratified by gender 9 : this same gender effect was observed for all headaches 25 and nonmigrainous headaches. 13 The present study reflected this strong association of migraines with dementia in women; it was unable to assess potential gender differences because no male participants had dementia as well as a history of migraines.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations